Cosolvent Exclusion Drives Protein Stability in Trimethylamine N-Oxide and Betaine Solutions - Ganguly, Pritam; Bubák, Dominik; Polák, Jakub; Fagan, Patrik; Dračínský, Martin; van der Vegt, Nico F A; Heyda, Jan; Shea, Joan-Emma (The journal of physical chemistry letters, 2022)
Using a combination of molecular dynamics simulation, dialysis experiments, and electronic circular dichroism measurements, we studied the solvation thermodynamics of proteins in two osmolyte solutions, trimethylamine N-oxide (TMAO) and betaine. We showed that existing force fields are unable to capture the solvation properties of the proteins lysozyme and ribonuclease T1 and that the inaccurate parametrization of protein-osmolyte interactions in these force fields promoted an unphysical strong thermal denaturation of the trpcage protein. We developed a novel force field for betaine (the KBB force field) which reproduces the experimental solution Kirkwood-Buff integrals and density. We further introduced appropriate scaling to protein-osmolyte interactions in both the betaine and TMAO force fields which led to successful reproduction of experimental protein-osmolyte preferential binding coefficients for lysozyme and ribonuclease T1 and prevention of the unphysical denaturation of trpcage in osmolyte solutions. Correct parametrization of protein-TMAO interactions also led to the stabilization of the collapsed conformations of a disordered elastin-like peptide, while the uncorrected parameters destabilized the collapsed structures. Our results establish that the thermodynamic stability of proteins in both betaine and TMAO solutions is governed by osmolyte exclusion from proteins.
Keywords: Muramidase; guanyloribonukleasa; termodynamika; roztoky; Water; Thermodynamics; methylaminy; muramidasa; Solutions; Methylamines; Betaine; Ribonuclease T1; Protein Stability; betain; stabilita proteinů; voda